Interactions between p53 and MDM2 in a mammalian cell cycle checkpoint pathway. - Chen, C Y (1994)
Normal p53 function is required for optimal arrest of cells in the G1 phase of the cell cycle following certain types of DNA damage. Loss of this cell cycle checkpoint may contribute to tumor development by increasing the number of genetic abnormalities in daughter cells following DNA damage. The MDM2 protein is an endogenous gene product that binds to the p53 protein and is able to block p53-mediated transactivation of cotransfected reporter constructs; thus, interactions between MDM2 and p53 in this checkpoint pathway following ionizing irradiation were examined. Though increases in p53 protein by DNA damage were not abrogated by MDM2 overexpression, increased levels of MDM2, resulting either from endogenous gene amplification or from transfection of an exogenous expression vector, were associated with a reduction in the ability of cells to arrest in G1 following irradiation. In addition, expression of endogenous MDM2 was enhanced by ionizing irradiation at the level of transcription in a p53-dependent fashion. These observations demonstrate that MDM2 overexpression can inhibit p53 function in a known physiologic pathway and are consistent with the hypothesis that MDM2 may function in a "feedback loop" mechanism with p53, possibly acting to limit the length or severity of the p53-mediated arrest following DNA damage.